Optical measurements of geometrical accuracy of gears - Świerek, Agata; Nowakowski, Paweł; Pietrasiak, Wiktor; Góral, Piotr; Marciniak-Podsadna, Lidia; Wieczorowski, Michał (Metrology and Measurement Systems, 2026)
The article presents the results of comparative tests of gear wheels based on non-contact and contact measurement methods. Comparative tests were performed on selected cylindrical gear wheels with straight teeth which are spare parts for transmission mechanisms. The paper compares important geometric parameters of gear wheels, such as the total deviation of the tooth line, the single and total pitch deviation, and the radial run-out deviation of the teeth. An optical measurement method was applied using the general tools available in the GOM ATOS II coordinate scanner software. The measurement results obtained using the non-contact method were compared with the results of the contact method using aWenzelWGT 600 specialised machine for measuring gear wheels. Based on the analysis conducted, the comparability of the measurement results of gear wheels performed in Accuracy Class 10 according to the DIN 3961/62 standard was demonstrated for the considered measurement methods, while at the same time indicating significant differences in the geometric parameters obtained between the parts manufactured under the manufacturer’s licence and commercial substitutes.